Switching to subcutaneous zilucoplan from intravenous complement component 5 inhibitors in generalised myasthenia gravis: a phase IIIb, open-label study - Miriam Freimer; Urvi Desai; Raghav Govindarajan; Min K. Kang; Shaida Khan; Bhupendra Khatri; Todd Levine; Samir Macwan; Perry B. Shieh; Michael D. Weiss; Jos Bloemers; Babak Boroojerdi; et al. (Therapeutic Advances in Neurological Disorders)
Background: Zilucoplan, a peptide complement component 5 (C5) inhibitor, is self-administered as a subcutaneous (SC) injection, which offers an alternative to intravenous infusion of antibody-based complement C5 inhibitors. Objective: To evaluate subcutaneous zilucoplan in adults with acetylcholine receptor autoantibody-positive generalised myasthenia gravis (gMG) who switched from intravenous complement C5 inhibitors to zilucoplan. Design: MG0017 (NCT05514873) was a phase IIIb, open-label, single-arm study. Methods: Eligible patients had clinically stable gMG on an intravenous complement C5 inhibitor and were willing to switch to zilucoplan. Patients received a 12-week treatment period of daily subcutaneous zilucoplan 0.3 mg/kg. Incidence of treatment-emergent adverse events (TEAEs) was the primary endpoint. Change from baseline in the Myasthenia Gravis Activities of Daily Living (MG-ADL) score at Week 12 was a secondary endpoint. Treatment preference (Week 12) and treatment satisfaction (9-item Treatment Satisfaction Questionnaire for Medication (TSQM-9)) were both exploratory endpoints. Assessments by prior intravenous complement C5 inhibitor were conducted post hoc. Results: Twenty-six patients enrolled and received zilucoplan; 16 switched from eculizumab and 10 from ravulizumab. TEAEs occurred in 19/26 (73.1%) patients and were mostly mild in severity. At Week 12, least squares (LS) mean (95% confidence interval) MG-ADL scores improved from baseline by −1.15 (−2.11, −0.19), p  = 0.0217 and Quantitative MG (QMG) scores by −1.24 (−2.64, 0.16), p  = 0.0802. Clinically meaningful improvement from baseline in mean MG-ADL and QMG scores was observed at Week 12 among patients who switched from ravulizumab (−2.41 (−4.52, −0.30; p  = 0.0307) and −3.52 (−6.14, −0.90; p  = 0.0149), respectively). At Week 12, 76.9% ( n  = 20) patients preferred subcutaneous injection compared with intravenous infusion. Mean (standard deviation) changes from baseline in the TSQM-9 Global Satisfaction, Effectiveness and Convenience subscores at Week 12 were +19.410 (27.429), +13.889 (21.534) and +21.739 (19.955), respectively. Complement inhibition increased from baseline and was complete (>95%) by Week 2 and maintained to Week 12. Conclusion: Zilucoplan demonstrated a favourable safety profile. gMG symptoms improved during zilucoplan treatment; this was clinically meaningful for those switching from ravulizumab. Trial registration: ClinicalTrials.gov (NCT05514873); 22 August 2022. https://clinicaltrials.gov/study/NCT05514873